Role of dietary fiber and lifestyle modification in gut health and sleep quality - Bacha, Amjad Ali; Suhail, Muhammad; Awwad, Fuad A.; Ismail, Emad A. A.; Ahmad, Hijaz (Frontiers in Nutrition, 2024)
Dietary fiber has an immense role in the gut microbiome by modulating juvenile growth, immune system maturation, glucose and lipid metabolism. Lifestyle changes might disrupt gut microbiota symbiosis, leading to various chronic diseases with underlying inflammatory conditions, obesity, and its associated pathologies. An interventional study of 16 weeks examined the impact of psyllium husk fiber with and without lifestyle modification on gut health and sleep quality in people with centrally obesity (male=60 and femle=60), aged from 40 to 60 years, having WC ≥ 90cm (male) and WC ≥ 80cm (female) and no history of any chronic disease or regular medication, were subgrouped into three intervention groups, the psyllium husk fiber (PSH) group, the lifestyle modification (LSM) group, the LSM&PSH group and control group with equal gender bifurcation (male=15 and female=15). 24-hour dietary recall, gastrointestinal tract (GIT) symptoms, and sleep quality analysis data were collected on validated questionnaires. The analysis of variance and covariance were used for baseline and postintervention respectively. Student t-tests were applied for pre and post-intervention change on the variable of interest. The intervention effect on GIT health was highly significant (P<0.001). The mean GIT score of the LSM, PSH, and the LSM&PSH group were 2.99±0.14, 2.49±0.14, and 2.71±0.14, respectively, compared to the mean GIT score of the control group. No significant (P=0.205) effect of either intervention was observed on sleep quality. The study concluded that Psyllium husk fiber significantly improved the GIT symptoms while no significant effect on intervention was observed on sleep quality analysis.